Peningkatan Kegiatan Pembelajaran Menggunakan Model Learner Tee Match Tipe Partikel - Anggraini, Putri; Izzati, Normaily Dewi; Azizi, Ainun; Aziza, Wafiq; Fachriza, Muhammad Rifqy; Tolubaw, Andrido; Kurniawan, Heldi; Apriyanto, Wahyudi (Jurnal Ilmiah Dikdaya, 2023)
The background of this research is that the learning outcomes of elementary school students are still relatively low. To improve these learning outcomes, research is needed using cooperative learning methods, learner tee match type, particle type. This study uses the classroom action research (CAR) method which uses the research model design of Kemmis and Mc. Taggart. This research was conducted in October 2022. Based on the results of the research it can be concluded that the application of the learner tee match type of cooperative learning of this particle type is suitable for social studies learning in class VB SD Condongcatur Muhammadiyah can improve student achievement. Applying one type of cooperative learning model increases competition. The pre-cycle average learning rate was 32.39% (bad results) increased to 73.25% (good results) in cycle I.